A Review of Parameters, Performance Models, And Applications of Biofiltration Technology In Reducing H2S Compounds In The Air - Utari Yolla Sundari; Ifwarisan Defri; Tawaffani Qubra; Rawee Chiarawipa (Agroindustrial Technology Journal, 2023)
High-quality air is essential for human survival. The present-day has a negative effect on air quality. Air contamination from the harmful compound H2S is an important problem. The primary source of H2S discharges is the oil and gas industry, where it is a by-product of resource harvesting and processing. Further sources of H2S discharges into the atmosphere include mining, waste management, and fossil fuel burning. H2S generates a malodorous scent resembling that of decayed eggs, which can prompt respiratory discomfort and irritation in humans and animals. At elevated concentrations, it may induce toxicity and even fatalities. Biofiltration is one of the latest remarkable technological advances for mitigating this issue. This method employs microorganisms to convert H2S into less harmful compounds. Biofiltration offers the major benefit of low operational expenditure and minimal environmental impact. This paper contributes to our comprehension of the microbial parameters, designs, models, applications and processes that affect biofilter efficiency. Diffusion-based biofiltration models show greater efficacy in design systems. Furthermore, advances in media, including the use of hollow cylindrical particles, have increased the efficiency of biofiltration. Sulfur-oxidizing microorganisms, such as Thiobacillus sp., play a pivotal role in decreasing H2S compounds.Â It is crucial to regularly monitor and regulate moisture levels, pH, temperature, and nutrient content to secure optimal and consistent biofiltration performance. The technology's effectiveness and stability heavily depend on precise control of these parameters. Biofiltration technology is hailed as a promising approach to manage H2S compounds, safeguard air quality, and preserve human health and the environment.